Lost in the Design Space? Construct Validity in the Microfinance Literature - Lise Masselus; Christina Petrik; Jörg Ankel-Peters (Institute for Replication (I4R), 2024)
Our paper examines construct validity, an often neglected yet important element affecting the generalizability of individual study results. Construct validity deals with how the operationalization of a treatment corresponds to the broader construct it intends to speak to. The universe of potential operationalizations is referred to as the design space. As an empirical example, we systematically review 45 microfinance Randomized Controlled Trials to estimate the size of the design space. Variations in the treatment operationalization matter for the observed effect. We also show that most papers generalize from the operationalized treatment to a broad construct, mostly without acknowledging underlying assumptions.
Keywords: A11; C18; C93; D04; O12; O16; 330; causal inference; generalizability; meta-science; microfinance; systematic review